The impact of heart rate towards archery performance / Ahmad Syafiq Azim Saeri - Saeri, Ahmad Syafiq Azim (Faculty of Sport Science and Recreation, 2016)
Heart rate is one of the variable that indicates how well the performance in archery. The purpose of this study was to analyze the heart rate and accuracy performance of expert and novice archers in mock tournament, trying to verify if the experience contributes to a reduction in heart rate and increase the accuracy of archery performance. 30 UiTM Pahang archers participated in this study, 15 are expert and another 15 are novice. Before the experimental procedure starts, the participants were explained about the aim of the study. They were given 3 rounds of sighters (practice round not counted) and 2 rounds of scoring. The heart rates were taken immediately after the last arrow of the last round finished. The result shows an expert archers had a slightly lower heart rate, 116 bts min, in contrast with novice archers with heart rate of 122 bts min. Expert archers also shoot better with the mean of 107 points compared to novice archers with 103 points. It is possible the experience of archers contributes in lowering the heart rate and better accuracy performance in any situations.